The Efficiency of Special Knowledge in Criminal Proceeding - ABDIKAPBAROVNA ALIMOVA, Elvira (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
The problems of the definition and use of the special knowledge of the experts in the criminal procedure are studied in this article. The procedural status of the expert, the procedural and non-procedural forms of his or her participation in proceedings in criminal cases are subject to analysis and theoretical and legal assessment. A clear understanding of the concept, content and opportunities for the use of special knowledge in the criminal proceeding is necessary for the successful investigation of any criminal case. The special knowledge is characterized by a number of special features: it is not common, it is not publicly available; it can be obtained in the course of theoretical and practical professional training; it is repeatedly used; it is involved in the procedure in accordance with the law in case of need for this kind of knowledge; it constitutes the evidence in case of use in the procedural form. In the literature, the concept of special knowledge has repeatedly been subjected to study, but the unity of views has not been achieved. The points of view of various scientists concerning the concept and the content of the special knowledge used in the criminal proceeding are presented in this article. The opinions on the admissibility criteria and the reliability of the evidence obtained through the use of special knowledge are also provided. The use of the special knowledge, in general, has a significant impact on the entire averment procedure. The article deals with the novels, introduced by the new Criminal Procedure Code of the Republic of Kazakhstan (CPC RK), which entered into force on January 1th, 2015. The CPC RK contains the statutory enshrined definition of special knowledge. This allows distinguishing more clearly the knowledge of the experts, used in the criminal proceeding, from the common general knowledge. The abilities of conclusions and expert evidence in finding of the criminal case facts are quite significant. At the same time, the use of these abilities requires the investigators and the judges to understand clearly the idea of how the conclusion and the expert evidence should be evaluated and the facts, established by this evidence, should be evaluated.
Keywords: evidence, averment, justice, expert, professional, special knowledge, criminal proceeding